2017
DOI: 10.1371/journal.pone.0188566
|View full text |Cite
|
Sign up to set email alerts
|

A non-threshold region-specific method for detecting rare variants in complex diseases

Abstract: A region-specific method, NTR (non-threshold rare) variant detection method, was developed—it does not use the threshold for defining rare variants and accounts for directions of effects. NTR also considers linkage disequilibrium within the region and accommodates common and rare variants simultaneously. NTR weighs variants according to minor allele frequency and odds ratio to combine the effects of common and rare variants on disease occurrence into a single score and provides a test statistic to assess the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…Over the past decades, various studies have identified a role for common genetic variation on cytokine level and response, however a significant proportion of inter-individual variability remains to be determined [12][13][14][15]. Considering the increasing evidence that specific combinations of variants with variable frequencies can influence phenotypic variability [16][17][18], in particular for a combination of phenotypic characteristics that do not fit one specific clinical diagnosis [30], we hypothesized that the inter-individual variability in cytokine responses might be subjectable to same concept. For this purpose, we sequenced the coding regions of 48 genes related to the IL-1 pathway in almost 500 healthy individuals, and assessed IL-1ß and IL-6 levels in whole blood in response to in vitro LPS, PHA, C. albicans and S. aureus.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Over the past decades, various studies have identified a role for common genetic variation on cytokine level and response, however a significant proportion of inter-individual variability remains to be determined [12][13][14][15]. Considering the increasing evidence that specific combinations of variants with variable frequencies can influence phenotypic variability [16][17][18], in particular for a combination of phenotypic characteristics that do not fit one specific clinical diagnosis [30], we hypothesized that the inter-individual variability in cytokine responses might be subjectable to same concept. For this purpose, we sequenced the coding regions of 48 genes related to the IL-1 pathway in almost 500 healthy individuals, and assessed IL-1ß and IL-6 levels in whole blood in response to in vitro LPS, PHA, C. albicans and S. aureus.…”
Section: Discussionmentioning
confidence: 99%
“…With recent advancements in sequencing technologies, the ability to study the role of rare and low-frequency variants has remarkably improved, and its value has been proven in several studies. For instance, increasing evidence is showing that the combined effect of common-and rare variants could partially explain the missing heritability problem in complex diseases [16][17][18]. The relatively smallto-moderate effects of common variants can be significantly modified by the presence or absence of (multiple) rare variants [19], and thus could partially explain the 'missing heritability' in the interindividual variability in immune responses.…”
Section: Introductionmentioning
confidence: 99%
“…One method frequently used for region-based RVAA is the sequence kernel association test (SKAT) [15][16][17][18] . While the method has been useful in revealing rare variants and genomic loci of interest in complex traits and diseases-such as cardiovascular disease, body-mass index, height, and neurodegenerative diseases [19][20][21][22] -reproducing these results can be difficult.…”
Section: Introductionmentioning
confidence: 99%